Kematangan Beragama Pada Remaja Yang Melakukan Pernikahan Dini - Luzaina, Luzaina; Musfichin (Jurnal Studia Insania, 2024)
AbstractThis research aims to determine the religious maturity of teenagers who marry early in South Banjarmasin District, from the high rate of early marriage in South Banjarmasin District, Banjarmasin City. The research uses qualitative methods (qualitative research). The approach used in this research is descriptive qualitative. The results of this research state that in general the religious maturity of the research subjects has sufficient knowledge of religious values and rules, but in practice or practice it has not been implemented well and consistently. This can be seen from how busy the couple is in meeting their household needs, because the couple's income is not yet established. The factors behind the occurrence of early marriage (case study in South Banjarmasin District), namely: (a) Family environmental factors that maintain religious values and norms in society, so that children do not fall into sin and values. Deviant values in society, (b) The factor of freedom of association, because this is the factor that initiates the emergence of interactions between early married couples.Keywords: Religious Maturity, Adolescence, Early Marriage.